Finance basics : (Harvard Business Review Press, 2014)
Finance Basics explains the fundamentals simply and quickly, introducing you to key terms and concepts such as: How to navigate financial statements;How to weigh costs and benefits;What’s involved in budgeting and forecasting;How to gauge a company's financial health.